Monitoring Dynamic Cellular Redox Homeostasis Using Fluorescence-Switchable Graphene Quantum Dots - Li, Nan (2017)
Monitoring cellular redox homeostasis is critical to the understanding of many physiological functions ranging from immune reactions to metabolism, as well as to the understanding of pathological development ranging from tumorigenesis to aging. Nevertheless, there is currently a lack of appropriate probes for this ambition, which should be reversibly, sensitively, and promptly responsive to a wide range of physiological oxidants and reductants. In this work, a redox-sensitive fluorescence-switchable probe is designed based on graphene quantum dots (GQDs) functionalized with a chelated redox Fe2+/Fe3+ couple. The underlying mechanism is investigated and discussed. The high sensitivity and fast response are attributable to the fact that the GQD’s photoluminescence is highly sensitive to photon-induced electron transfer because of its ultrasmall size and associated prominent quantum confinement effect. Also taking advantages of GQDs’ excellent photostability, biocompatibility, and readiness for cell uptake, our reversibly tunable fluorescence probe is employed to monitor in real time the triggered dynamic change of the intracellular redox state. This addition to the limited arsenal of available redox probes shall be useful to the still poorly understood redox biology, as well as for monitoring environment or chemical processes involving redox reactions.